Natural history of premature thelarche: review of 60 girls - Jose R. L. Batubara; Adji Suranto; Sudigdo Sastroasmoro; Bambang Tridjaja; Aman B. Pulungan (Indonesian Pediatric Society, 2001)
In Indonesia report on the natural history of premature thelarche is very limited. Daily practice requires physicians to have some basic practical knowledge, among others the natural history of premature thelarche, in order to manage these patients properly. We reviewed data of 85 premature thelarche patients who visited our department from January 1989 until December 1998. Only 60 patients met the study criteria. The mean chronological age of the patients at diagnosis was 43.4 months. About half of these patients (31/60) were diagnosed before they were 2 years old. Half of the patients had bilateral breast involvement. The hormonal pattern showed 24/48 follicle stimulating hormone predominant-response. Most patients (33/47) showed normal plasma estradiol level. Bone age analysis was normal in 46/57 patients, and only 9 showed accelerated bone age. Pelvic ultrasonography showed prepubertal reproduction organs in 26/35. Vaginal smears showed signs of estrogenization with various degree of stimulation in 13 patients. At the end of observation the outcome of premature thelarche were: 31 regressed, 19 persisted, 6 had progressive breast development and 4 progressed to central precocious puberty. The initial clinical and laboratory characteristics of those who developed CPP varied. Among 31 premature thelarche patients who regressed, 21 had onset of breast enlargement before age of 2 years. In most of the regressed patients (20/31), regression occurred completely within the first year. Most premature thelarche patients with onset before 2 years will regress within one year after diagnosis.Â